Development of a scalable video compression algorithm - Khalifa, Othman Omran; Issa, Sinzobakwira; Olanweraju, Rashidah Funke; Al Khazmi, El Mahdi A (2012)
The development of multimedia propagations and applications has led to a greater expansion in the field of video transmission over a heterogeneous media as well as iterative delivery platforms with dedicated content requirements. It is known that conventional video coding systems encode video content with given bitrates adapted to a specific function or application. As a result, conventional video coding does not meet the fundamental requirements of the state-of-the-art flexible digital media application. Meeting the required bandwidth for video transmission is extremely complex resulting in poor video quality. The new technology H.264/AVC, based on scalable video coding appears as a new modus operandi that has the ability to satisfy the underlying requirements. In this paper a rate distortion optimized video frame dropping strategy which can be applied on active network nodes during high traffic intensity for H.264/AVC was developed. To improve the perceptual quality of coded video in a computation-constrained scenario, through controlling per-frame complexity, a rate-distortion optimised (RDO) rate control algorithm for encoding low bit rate video helped to achieve the target bitrates and PSNR using Lagrangian multiplier function. However simulation was conducted using JM and JSVM software. The choice of a scalable video coding framework in this context brings technical and economical advantages. The result shows that the managed complexity algorithm based on Lagrangian Multiplier function outperforms the normal encoder. The comparison between different video streams proves that the scalable video coding leads to good constructed video quality.